2015
DOI: 10.2169/internalmedicine.54.4935
|View full text |Cite
|
Sign up to set email alerts
|

Two Cases of Adult-onset Still's Disease Treated with Tocilizumab that Achieved Tocilizumab-free Remission

Abstract: There have been many previously reported cases of adult-onset Still's disease (AOSD) which were successfully treated with tocilizumab (TCZ). However, the efficacy and safety of TCZ therapy for AOSDassociated macrophage activation syndrome (MAS), and the optimal duration of TCZ therapy, remain unclear. We herein report two cases of refractory AOSD, one of which was associated with MAS. These two patients were treated with TCZ, and the withdrawal of TCZ was planned according to the serum interleukin-6 level, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…We reviewed the literature for reports on the treatment of AOSD-associated MAS with biologics [ 22 27 ] ( Table 1 ). We searched for literature in English and Japanese languages published up until December 2015 in PubMed database for eligible articles that simultaneously met with Medical Subject Headings terms of AOSD and MAS/HPS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We reviewed the literature for reports on the treatment of AOSD-associated MAS with biologics [ 22 27 ] ( Table 1 ). We searched for literature in English and Japanese languages published up until December 2015 in PubMed database for eligible articles that simultaneously met with Medical Subject Headings terms of AOSD and MAS/HPS.…”
Section: Discussionmentioning
confidence: 99%
“…IL-18 acts upstream of IL-6 in the inflammatory cytokine cascade [ 14 , 31 ]. Therefore, TCZ monotherapy might be ineffective, as it is unable to fully inhibit the inflammatory cytokines downstream of IL-18 [ 27 ]. The inhibition of a single cytokine pathway may cause an unfavorable imbalance in the cytokine network involved in AOSD-associated MAS [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…No published prospective clinical trials evaluating TCZ in AOSD are available, but promising efficacy results have been observed in several case reports and retrospective analyses [84][85][86][87]. Improvements in clinical (fever, rash, and myalgia) and laboratory (ESR and CRP) manifestations were observed after treatment with TCZ in a review of 24 cases of AOSD in Korean patients [88].…”
Section: Other Diseasesmentioning
confidence: 99%
“…[1,27] Indeed, tocilizumab has been shown to be effective for refractory AOSD around the world. [25,2833] However, it remains unknown whether tocilizumab would be effective for SIRS complicating AOSD. Although SIRS complicating AOSD is extremely rare and mild cases are responsive to high-dose steroids, [8,34] it can also be fatal.…”
Section: Discussionmentioning
confidence: 99%